KONSERVASI ENERGI SISTEM PENCAHAYAAN UNTUK KENYAMANAN RUMAH TINGGAL DUA LANTAI MENGGUNAKAN SIMULASI DIALUX EVO - Matalata, Hendi; Wustha Johar, Leily; Manap, Abdul; Yulianto, Didik (Jurnal Teknologi dan Vokasi, 2024)
In order to improve energy conservation efforts and comfort in building structures, all building managers such as professional associations, consultants, contractors, suppliers can apply the concepts of lighting system design procedures in building structures that can be utilized by planners as required by SNI 6197:2020. In this study, technical calculations were carried out using dialux evo software to obtain lighting intensity based on the function of the residential room. From the results of the research that has been carried out, the minimum average lighting level of the lighting intensity of each room function in natural lighting during the day, there are 2 rooms that meet the requirements, namely the bedroom and bathroom (KM1, for this purpose artificial lighting is carried out using lamps, at night the minimum average lighting level on the first floor gets a large lighting intensity of the room that meets the requirements based on SNI 6197:2020 which is required for each room function. To save energy, the bedroom and bathroom (KM1) switches are in the off position during the day while at night the switches for each room are in the on position.